In every end, there is also a beginning: experiences of career transitions through sport - Nash, C.; Thompson, M. (International Sport Coaching Journal, 2024)
In sport, as in life, people experience transitions on a regular basis. This exploratory research examined the experience of the transitional process within sport using a qualitative methodology. The seven participants had worked within their sport for over 30 years, first as an athlete, then a coach, and finally a coach developer. Semistructured interviews with each participant (x2) allowed for exploration of their experiences of changing roles within their organizations and revealed three themes: importance of timely support, ongoing professional conversations, and where am I going with this? These themes, exemplified by the use of direct quotes from the participants, were used to provide context and deeper understanding of the transition from athlete to coach to coach developer. The participants revealed a certain degree of serendipity, due to a lack of structure and process in their experiences. As a result, we suggest some practical steps that organizations could adopt to assist in this process.